A prayer for the crown-shy eaudiobook - Chambers, Becky (Monk & Robot, 2022)
"Tender and healing... I'm prescribing a preorder to anyone who has ever felt lost. Stunning, kind, necessary." —Sarah Gailey on book 1: A Psalm for the Wild-Built "This hopeful listen, full of humor, illuminates a world listeners will yearn to return to." -AudioFile on A Prayer for the Crown-Shy A Prayer for the Crown-Shy is a story of kindness and love from one of the foremost practitioners of hopeful SF. After touring the rural areas of Panga, Sibling Dex (a Tea Monk of some renown) and Mosscap (a robot sent on a quest to determine what humanity really needs) turn their attention to the villages and cities of the little moon they call home. They hope to find the answers they seek, while making new friends, learning new concepts, and experiencing the entropic nature of the universe. Becky Chambers's new series continues to ask: in a world where people have what they want, does having more even matter? A Macmillan Audio production from Tor.com